Exploring the impact of supplementary schools on Black and Minority Ethnic pupils' mainstream attainment. (10th January 2013) - Maylor, Uvanney; Rose, Anthea; Minty, Sarah; Ross, Alistair; Issa, Tozun; Kuyok, Kuyok Abol
<x xml:space="preserve">Abstract</x> This paper reports findings from a study commissioned by the (then) Department for Children, Schools and Families. The research mapped the provision, and explored the impact, of supplementary schools and aimed specifically to develop further understanding as to how supplementary schools might raise the attainment of Black and Minority Ethnic pupils. Drawing on a national survey and case study data from 12 supplementary schools, we highlight a range of perceived impacts identified by teachers, pupils and parents and problematise the concept of impact. We identify the unique contribution and impact that supplementary schools make to the mainstream school attainment of pupils from diverse (linguistic, cultural, ethnic) backgrounds. We suggest that there is much to be learnt by the mainstream school sector about the difference supplementary school education makes to minority ethnic children, while questioning whether mainstream indicators of impact should be applied to supplementary schools.